Public reporting format transformation in the concept of information transparency of the Performance of Economic Entities - I. V. Safonova (Учёт. Анализ. Аудит)
The concept of corporate transparency in the business world is becoming a “new philosophy” in the system of communication interaction between business and stakeholders; at the same time, the most effective channel for an open dialogue is the reporting of economic entities. The demand of modern users has shifted towards the valueand risk-oriented nature of information disclosure and the possibility of using interactive tools for navigation and data visualization. Understanding this leads the professional community to an active search for new solutions to create an optimal model of public reporting and the very architecture of information support for companies. The purpose of the study is to develop an integrated concept of accounting and corporate reporting based on the principles of information transparency, ecosystem, connectivity, and manufacturability. In the course of the work, the methods of deduction and induction, logical and structural analysis, empirical research, content analysis, comparison and grouping were used. The article presents a comprehensive review of the developments of Russian and foreign scientists in the field of corporate reporting and highlights the key areas of its development. The author has studied the methodological, organizational and technological aspects of creating a modern architecture for information support of the activities of economic entities within the framework of the concept of a single corporate reporting format as an element of the business information ecosystem. As a result, a model of a complexly structured level of disclosure of reporting data was proposed by the author in the form of a single, unified digital information and analytical platform built on the principles of differentiation of approaches to disclosure, typification of the level of information transparency and definition of indicators that should be reflected in the reporting. The system of mandatory and voluntarily disclosed reporting forms has been formulated, representing the modern information outline of economic entities, systemically interconnected, linked and integrated with each other in the format of a single, unified corporate reporting. The study may be of interest to national regulators, scientific, professional and business communities.